2006
DOI: 10.1093/her/cyl069
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of environmental correlates of obesity-related dietary behaviors in youth

Abstract: There is increasing interest in the role the environment plays in shaping the dietary behavior of youth, particularly in the context of obesity prevention. An overview of environmental factors associated with obesity-related dietary behaviors among youth is needed to inform the development of interventions. A systematic review of observational studies on environmental correlates of energy, fat, fruit/vegetable, snack/fast food and soft drink intakes in children (4-12 years) and adolescents (13-18 years) was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

43
392
5
13

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(453 citation statements)
references
References 74 publications
43
392
5
13
Order By: Relevance
“…The review shows that home availability, family rules (demand/allow) and parental encouragement were positively associated with children's fruit and vegetable consumption and that parental modelling and parental intake were positively associated with children's consumption of fruit and FJV. Our findings support the work of others (18,19) that parental intake and home availability are strongly related to children's eating behaviours. The importance of parental intake, parental modelling and home availability on children's food consumption is also supported by the qualitative work of Campbell et al (23) who found that parents believed eating with their children was important in order to model eating behaviours and also that making food available was likely to influence child's food consumption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The review shows that home availability, family rules (demand/allow) and parental encouragement were positively associated with children's fruit and vegetable consumption and that parental modelling and parental intake were positively associated with children's consumption of fruit and FJV. Our findings support the work of others (18,19) that parental intake and home availability are strongly related to children's eating behaviours. The importance of parental intake, parental modelling and home availability on children's food consumption is also supported by the qualitative work of Campbell et al (23) who found that parents believed eating with their children was important in order to model eating behaviours and also that making food available was likely to influence child's food consumption.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Rasmussen et al (19) found that parental intake and home availability/accessibility were some of the most consistently supported determinants of fruit and vegetable consumption in young people. The current review aims to develop and add to the findings of Rasmussen et al (19) and van der Horst et al (18) by updating the evidence for fruit and vegetable consumption, focusing specifically on family correlates and by reporting the results and findings for fruit and vegetables separately. This review focuses on school-aged children (6-18 years) because this covers the complex and dynamic time periods where behaviours may begin to be influenced by other social and environmental factors.…”
Section: Adolescents Children Family Correlates Fruit Vegetablesmentioning
confidence: 99%
“…In addition to the supportive effect of Overt Control and Covert Control on decreasing snack (and SSB) intake, Covert Control was also supportive in increasing child fruit intake. This suggests that parents who exert higher levels of Covert Control might replace the home availability of unhealthy snacks by home availability of fruit, which is positively related to fruit intake (15,20,22,52) . Consistent with previous findings (23) , Encouragement was negatively related to child energy-dense snack intake, indicating that parental encouragement might be influenced by health beliefs: parents encourage their children's interest in and curiosity for a variety of healthy foods, resulting in the consumption of less unhealthy foods (23,49) .…”
Section: Discussionmentioning
confidence: 99%
“…where the healthy behavioural options are more and unhealthy options are less easily available and accessible (13)(14)(15) . For adolescents a supportive and facilitating home environment is likely to be of crucial importance where dietary behaviour is concerned (16) .…”
mentioning
confidence: 99%